2003
DOI: 10.1536/jhj.44.943
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dental Status With Blood Pressure and Heart Rate in 80-Year-old Japanese Subjects.

Abstract: SUMMARYPeriodontal disease is one of the main reasons for the loss of teeth in elderly subjects, and it has been reported that periodontal disease is a potential risk factor for cardiovascular disease. However, little data is available regarding the association between dental status and blood pressure or heart rate in elderly individuals, particularly in subjects over 80 years old. We studied the cross-sectional association between dental status and blood pressure or heart rate in 499 Japanese (195 men and 304… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
6
2
Order By: Relevance
“…Matsumura et al. 12 reported a lower bpm than ours in an elderly community‐dwelling group in Japan, but this was of a greater average age (80 years), and the heart rate at rest slows slightly with age.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Matsumura et al. 12 reported a lower bpm than ours in an elderly community‐dwelling group in Japan, but this was of a greater average age (80 years), and the heart rate at rest slows slightly with age.…”
Section: Discussioncontrasting
confidence: 61%
“…Matsumura et al. 12 measured the blood pressure and heart rate of 499 community‐dwelling 80‐year‐old in Japan and recorded an average heart rate of 69.6 bpm (beats per minute), an average systolic pressure of 149.6 mmHg and an average diastolic pressure of 78.5 mmHg. They also found an inverse relationship between the number of teeth and the heart rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of this study showed an average of 71.4 bpm, with maximum and lowest values of 100 and 43, respectively. The results of this study are in agreement with those of previous studies, ranging from 60 to 100 bpm at rest 9 and an average of 69.6 bpm 17 . No correlation was observed between blood pressure and AUDIT scores, which differs from a classic study 19 that evaluated the influence of alcohol consumption and blood pressure on 83,947 adult patients and found that regular use of three or more drinks of alcohol per day should be considered a risk factor for hypertension due to its increase in systolic and diastolic pressures as well as higher prevalence of pressures higher than 160/95 mmHg.…”
Section: Discussionsupporting
confidence: 93%
“…In Campinas, SP, Brazil, Zeitune et al 16 found a hypertension prevalence of 51.8% among 426 adults aged 60 years or older, with higher incidence in women (55.9%). In Japan, blood pressure was measured in 499 elderly community dwellers, with a mean age of 80 years, and mean systolic and diastolic blood pressures were 149.6 mmHg and 78.5 mmHg respectively 17 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that a higher percentage of 8020 achievers were satisfied with life and felt healthy 13) . There is a close relationship between number of teeth and heart rate 10) . Masticatory ability is more important to QOL than number of retained teeth 2) .…”
Section: Discussionmentioning
confidence: 93%